(-23) x (42) = (-21) x 23 x _________ *​

Question

(-23) x (42) = (-21) x 23 x _________ *​

in progress 0
Athena 1 month 2021-08-13T01:51:50+00:00 2 Answers 0 views 0

Answers ( )

  1. Emma
    0
    2021-08-13T01:53:04+00:00

    Let the unknown number be x
    -23 x 42= -966
    -21 x 23 = -483
    -966 = -483x
    -966/-483=2
    2 is your answer

    Hope this helps!

  2. Emma
    0
    2021-08-13T01:53:38+00:00

    Answer:

    (-23)×(42)=(-21)×23×______

    -966=483

    is not equal so

    (-23)×42=(-21)×23×2

    that is your answer

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )